A fabrication of three-dimensional multi-assembling platform based on polyimide matrix. (21st November 2019) - Li, Renke; Li, Chengfeng; Liu, Yao; Liang, Bo; Hu, Jianghuai; Zeng, Ke; Yang, Gang
Abstract: The potential of polyimide as a matrix of three dimensional frameworks was demonstrated and discussed. Hydrophilic cellulose nanocrystals (CNC), a renewable nanofiller, and copper nanoparticles were anchored into the polyimide frameworks, based on characteristics of two-step procedure of polyimides. The influences of the addition of CNC on properties and morphological evolution of the porous framework were studied. Furthermore, an "incomplete thermal imidization" strategy was utilized to reserve carboxylate groups of the precursor of the polyimide, enabling the constructed framework precursor to further capture Cu 2+ even at low concentration (80 ppm). Then related metal nanoparticles can form in situ on the porous framework through a facile thermal imidization reaction, which is called a "secondary-assembly" strategy here. The presented strategy may be further applied to assembly more functional nanoparticles, and build a platform material with manifold application potential such as oil clean-up, high performance catalyst and removal and reuse of heavy metals. Graphical abstract: Image 1 Highlights: Polyimide was used to fabricate multifunctional porous frameworks. The percentage of CNC can regulate microscopic morphology of the frameworks. A "secondary-assembly" strategy was presented to assemble nanoparticles on porous polyimide frameworks. A method of reuse and removal for heavy metal ions was demonstrated.